O ensino médio profissional nas escolas do Maciço de Baturité: uma abordagem sociológica para a sala de aula - Soares, Estelany Silveira (2024)
This work aims to analyze the meanings that high school students from professional schools in the Maciço de Baturité region, Ceará, attribute to the last stage of basic education and, based on this, present a sociological approach to the discussion about high school. professional in the classroom. The research was carried out by applying 620 questionnaires to students from five professional high schools in the Massif de Baturité region. This material provided support to produce a teaching plan for teachers, based on didactics for historical-critical pedagogy, with professional secondary education itself as the object of problematization. The teaching plan aims to build a class that allows students to recognize this stage as something socially constructed and also a space for dispute between different societal projects. Considering that high school itself is a stage historically marked by numerous contradictions and challenges that refer to its identity, expansion, obligation and curricular structure, it is important that the student understands these processes sociologically and problematizes the consequences of recent changes. It is expected that teachers and students will be able to give new meaning to this stage beyond the acquisition of knowledge and skills relevant to entry into university and/or the job market, and work towards the formation of a more realistic and critical awareness of society.